Implementasi Point of Sale Pada Cora Petshop Menggunakan Metode Agile dan Scrum Framework - Dwi Auditira; Agung Triayudi; Deny Hidayatullah (Journal of Information System Research (JOSH), 2023)
Petshop is a place of business that sells pet needs and supplies. Cora Petshop, whose head office is at Jalan. Batu Raya 1 No.9 Setiabudi, South Jakarta is a shop that sells animal supplies and needs that started a business in 2020 through online media. In the online trading system, it is considered risky and becomes a consideration for consumers in making purchases. One of the main factors of business success is from customers. This is the basis for Cora Petshop to run its business face to face. Point of Sale is one of the many systems used as a means of payment in various existing businesses. Transaction activities between the Point of Sale System and customers that occur in the business world. In this study, a Point of Sale system application has been made for business support for Cora Petshop, with the system development method using Agile Software Development along with the Scrum framework contained in Agile techniques. The results that are applied to the Point of Sale are successful in making transactions, recording incoming and outgoing reports of goods, and are suitable for use.